Examining ACT process measures with cognitive interviewing - Wright, Jessica (2019)
Acceptance and Commitment Therapy (ACT) proposes that psychological distress manifests as experiential avoidance (the behaviour of moving away from or avoiding perceived negative thoughts, feelings, and physical sensations) which can lead to a reduction in personally meaningful pursuits. A primary focus of ACT is to reduce experiential avoidance by promoting psychological flexibility. With ACT being used more widely in clinical practice and research, it is important that instruments measure processes as intended. Cognitive interviewing (CI) is an established applied qualitative method for examining and improving the validity of psychological measures. Utilising concurrent or retrospective interview techniques, the method examines how individuals interpret, understand, and respond to psychometric items, to determine whether they target expected domains and processes. The study had four aims: (1) To explore how respondents understand, interpret, and respond to items of the CompACT and the AAQ-II; (2) To explore how responses on the CompACT and the AAQ-II correspond with the intended ACT processes being measured and how these relate to the literature relating to psychological flexibility; (3) To highlight any areas of response error or problems with items on the CompACT and the AAQ-II; (4) To compare any differences in responses between the concurrent and retrospective CI groups. Twenty-six ACT-naïve individuals completed both measures and took part in either retrospective or concurrent cognitive interviews. Responses to all CompACT items corresponded with its putative three-factor conceptualization of psychological flexibility. Responses to six AAQ-II items corresponded with concepts of experiential avoidance and committed action; mapping for one item was unclear. Low frequency problems (e.g., unclear wording) were found with items on both measures, and both appeared to target intended (but varied) ACT constructs. No clear difference was found between the two CI groups (retrospective or concurrent). Findings seemingly support the CompACT as a conceptually broader measure of psychological flexibility, while the AAQ-II appears more targeted on experiential avoidance-related domains. The study adds to the discussion about CI methodology and best practice guidelines for the approach.